2018
DOI: 10.3766/jaaa.17004
|View full text |Cite
|
Sign up to set email alerts
|

Audiology Assistants: Results of a Multicenter Survey

Abstract: Within a small sample size of pediatric and life-span facilities, 14 of 22 centers used AAs to perform a variety of direct patient care, indirect patient care, and clerical duties. Based on the duties recommended within the American Speech-Language-Hearing Association guidelines and by many states, expanded employment of AAs, as well as expansion of assigned duties should be considered. Data are needed to determine the appropriate ratio of AAs to audiologists within different settings and to determine the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Improvements in efficiency of audiology clinics were demonstrated by Hamill and Andrews (2016 8 ), who found AAs deployed within the Veteran's Affairs system significantly increased patient capacity and decreased per patient cost by 60%. Despite potential benefits, Karzon et al (2018 16 ) reported audiologists have not embraced service-extenders out of concern for quality, loss of audiology positions, and patient confusion relative to audiologists' role. A review of extant literature suggests audiologists have been slow to change service delivery models to improve patient capacity and clinic efficiency (ASHA, 2012 15 ; Karzon et al, 2018 16 ; Hearing Health & Technology Matters [HHTM], 2018 17 ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvements in efficiency of audiology clinics were demonstrated by Hamill and Andrews (2016 8 ), who found AAs deployed within the Veteran's Affairs system significantly increased patient capacity and decreased per patient cost by 60%. Despite potential benefits, Karzon et al (2018 16 ) reported audiologists have not embraced service-extenders out of concern for quality, loss of audiology positions, and patient confusion relative to audiologists' role. A review of extant literature suggests audiologists have been slow to change service delivery models to improve patient capacity and clinic efficiency (ASHA, 2012 15 ; Karzon et al, 2018 16 ; Hearing Health & Technology Matters [HHTM], 2018 17 ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite potential benefits, Karzon et al (2018 16 ) reported audiologists have not embraced service-extenders out of concern for quality, loss of audiology positions, and patient confusion relative to audiologists' role. A review of extant literature suggests audiologists have been slow to change service delivery models to improve patient capacity and clinic efficiency (ASHA, 2012 15 ; Karzon et al, 2018 16 ; Hearing Health & Technology Matters [HHTM], 2018 17 ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation